1976
DOI: 10.1111/j.1469-1809.1976.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics and infertility in man*: II. Testicular histology and meiosis

Abstract: Within a group of 207 subfertile men, selected for testicular biopsy, histological investigations were made successfully in 194 chromosomally normal and 7 chromosomally abnormal individuals. Fifty-two per cent of men with a normal karyotype showed normal testicular histology, 31% showed a general depression of spermatogenesis and 8% showed deficiency in the late stages. Ten per cent had only Sertoli cells in the testis. The range of testicular conditions seen in the chromosomally abnormal men was similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 28 publications
0
43
2
Order By: Relevance
“…Chandley et al [23] showed a reduced proportion of spermatids and spermatozoa on testicular biopsy in subfertile balanced translocations carriers. Balanced, structural chromosome aberrations seldom result in azoospermia [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Chandley et al [23] showed a reduced proportion of spermatids and spermatozoa on testicular biopsy in subfertile balanced translocations carriers. Balanced, structural chromosome aberrations seldom result in azoospermia [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, histone deacetylation seems to play a key role in preventing aneuploidy during female meiosis. In somatic cells and mammalian male germ cells, a spindle assembly checkpoint monitors chromosome alignment and spindle integrity during cell division (19,20). In the absence of proper chromosome alignment, the cell cycle is arrested or anaphase is delayed, allowing the cell to correct errors that might otherwise produce aneuploid progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Studies at these meiotic stages are scarce, owing to the difficulty of obtaining testicular tissue. Meiotic analyses carried out on fertile and infertile men described abnormal chiasma count and numerical chromosome abnormalities (Skakkebaek et al, 1973;Chandley et al, 1976;Koulischer et al, 1982;Egozcue et al, 1983;Laurie et al, 1985;Guichaoua et al, 1986;Uroz et al, 2009Uroz et al, , 2011 but they were not focused on studying non-disjunction mechanisms.…”
Section: Introductionmentioning
confidence: 99%